Penerapan Model Problem Based Learning (PBL) Berbatuan Media Canva untuk Meningkatkan Hasil Belajar Matematika Kelas IV - Choir, Sigit Miftachul; Reffiane, Fine (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Abstract As technology develops in the industrial era 4.0, it has a significant impact on the world of education. Learning is starting to be directed towards the use of learning media that is able to attract students' interest in learning. Especially learning mathematics in elementary school. Learning mathematics is known as a difficult, boring and monotonous lesson. Even students at elementary school level are less interested in this lesson. This can be seen from the relatively low mathematics learning outcomes. The aim of this research is to improve student learning outcomes in the learning process through the application of the Problem Based Learning model assisted by Canva media whether it meets the KKM or not. This type of research is quantitative with a pre-experimental design method with the design form used being One-Group Pretest-Potstest Design. The location of this research is SDN Pandeanlamper 03 with a sample size of 28 students in class IV. Hypothesis testing in this research uses the Paired Sample T Test which shows Sig. 0.000 < 0.05, so according to the decision making in the Paired Sample T Test it can be concluded that H0 is rejected and Ha is accepted. This shows that there is a significant influence on learning outcomes using the PBL learning model assisted by Canva media.